2006
DOI: 10.1121/1.2188354
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic impedance of perforations in contact with fibrous material

Abstract: Acoustic impedance of perforations in contact with fibrous material, as well as air alone, is experimentally determined in the absence of mean flow. Different porosities ͑2.1, 8.4, 13.6, and 25.2 %͒ and hole diameters ͑0.249 and 0.498 cm͒ are applied for perforations, along with two fiber filling densities ͑100 and 200 kg/ m 3 ͒ to illustrate the effect of variations in such parameters on the perforation impedance. A modified impedance tube setup is developed for the measurement of the acoustic impedance of pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 18 publications
2
35
0
Order By: Relevance
“…A comparison of these results with those of the MPP coupled to an air cavity and a rigid wall leads to the conclusion that the presence of the porous material behind the MPP causes a shift of the limit Reynolds number towards the low ranges regime. This is explained by the fact that the porous material behind the MPP increases the system resistance [2,4] as stipulated earlier. The measurements and prediction are also in good agreement.…”
Section: International Journal Of Engineering and Technologymentioning
confidence: 93%
See 1 more Smart Citation
“…A comparison of these results with those of the MPP coupled to an air cavity and a rigid wall leads to the conclusion that the presence of the porous material behind the MPP causes a shift of the limit Reynolds number towards the low ranges regime. This is explained by the fact that the porous material behind the MPP increases the system resistance [2,4] as stipulated earlier. The measurements and prediction are also in good agreement.…”
Section: International Journal Of Engineering and Technologymentioning
confidence: 93%
“…Under low sound pressure levels, such assemblies are known [2][3][4] to result in shifting the resonance frequency, which is mainly induced by the perforated plate, to lowfrequency bands and enhance the acoustic absorption near the resonance frequency. The absorption performance of perforated plates alone is known [5] to be enhanced when the perforation sizes approach the boundary layer thickness sizes (submillimetric sizes very often).…”
Section: Introductionmentioning
confidence: 99%
“…The correction is based on replacing the density of air with the equivalent density ρm. Lee et al [40] also concluded that this procedure captures the effect of the absorbent material on the perforated duct. As shown in reference [34], good agreement between experimental and numerical silencer transmission loss is achieved considering an expression of the form…”
Section: Non-uniform Acoustic Impedance Of the Perforated Surfacementioning
confidence: 99%
“…(47)- (50), however, do not include the effect of the absorbent material on the acoustic impedance of the perforated duct. This influence has received attention in several works [39][40][41]. In reference [39], the effect of a fibrous material on the impedance of the perforated surface was measured and the authors suggested adding a correction to the impedance obtained in the absence of material.…”
Section: Non-uniform Acoustic Impedance Of the Perforated Surfacementioning
confidence: 99%
See 1 more Smart Citation